2014
DOI: 10.1089/ten.tea.2013.0295
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Electrophysiological Function and Control of Neurite Outgrowth on Electrospun Polymer Nanofibers Are Cell Type Dependent

Abstract: Modeling of cellular environments with nanofabricated biomaterial scaffolds has the potential to improve the growth and functional development of cultured cellular models, as well as assist in tissue engineering efforts. An understanding of how such substrates may alter cellular function is critical. Highly plastic central nervous system hippocampal cells and non-network forming peripheral nervous system dorsal root ganglion (DRG) cells from embryonic rats were cultured upon laminin-coated degradable polycapro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…In agreement with others using rodent cortical-and hippocampal-derived neural cells and the biodegradable and widely used biomaterials: PLGA, PCL and PLLA [8] [9] [10], the human cells used here displayed very good survival at the surfaces made of PLLA. Since we chose to use neurospheres as a seeding method it was not possible to quantify exact numbers of cells surviving the culture period.…”
Section: Attachment and Survival Of Hnpc At Plla Substratessupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with others using rodent cortical-and hippocampal-derived neural cells and the biodegradable and widely used biomaterials: PLGA, PCL and PLLA [8] [9] [10], the human cells used here displayed very good survival at the surfaces made of PLLA. Since we chose to use neurospheres as a seeding method it was not possible to quantify exact numbers of cells surviving the culture period.…”
Section: Attachment and Survival Of Hnpc At Plla Substratessupporting
confidence: 90%
“…expression of markers for late neuronal differentiation, such as MAP-2 and neurofilament as well as for synaptic formation (e.g., the markers synaptophysin and SV2 [29]. Studies of electrical activity are also needed, and Bourke at al previously reported maintained electrical activity over time in rodent CNS-derived neurons, using patch-clamp techniques [8].…”
Section: Topography Influence Hnpc Phenotypic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary hippocampal neurons were isolated post-mortem from the brains of E18 Sprague Dawley rat fetuses, using established protocols. 35 Glass coverslips, with a diameter of 9 mm, were acid-washed, rinsed with 80% ethanol, allowed to dry, and then coated overnight with either PLO control or the self-assembled scaffolds to test their ability to promote neuron adhesion, survival, and function. Next morning, the coating was removed by Â3 washing in HBSS and kept moist until the cells became available (see below).…”
Section: Methodsmentioning
confidence: 99%
“…In most of these studies, the primary neurons were cultured in culture dish or on glass slides with or without astrocytes [5]. It has been shown, however, that the neural growth and its functional performance are critically dependent on the culture conditions, especially the components and mechanical properties of the substrate [6,7], while the culture dish method is not sufficiently flexible to achieve the optimal conditions. In principle, mimicking the in vivo cell microenvironment can lead to significant improvement of the culture conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%